Implementation of Biodiversity Centre In Improving Naturalistic Intelligence of Children in 5-6 Years Old at PAUD An Najah, Jatinom Subdistrict, Klaten Regency - Kurniawati, Yuyun; Adiarti, Wulan (Indonesian Journal of Early Childhood Education Studies, 2017)
The purpose of the study was to find out the implementation of biodiversity centre in improving naturalistic intelligence of children in 5-6 years old. The study was conducted in PAUD An Najah, Jatinom Subdistrict, Klaten Regency. The study used 30 children as the samples of the study. The study used one group pretest-posttest design as its experimental design. Data collecting utilized the purposive sampling. The result showed the naturalistic intelligences improvement of children in 5-6 years old. Based on the t value measurement, the study found –ttable > tcount > t table included (2.04 > - 28.25 or 28.25 > 2.04), with sig = 0.000, so Ho was declined and Ha was accepted. It explained that there was significant difference of the naturalistic intelligences of children in 5-6 years old after using biodiversity centre implementation.